Interpreting Corporate Zakat as Trade Zakat: The Construction of Islamic Legal Knowledge and Zakat Collection Practices at Baitulmaal Munzalan Indonesia - Khamim, Khamim; Adithya, Rizky; Waldan, Raziki; Adzkiya’, Ubbadul; M. Nur, Uray (Institut Agama Islam Negeri (IAIN) Pontianak, 2025)
Corporate zakat, or zakat levied on legal entities, is a contemporary phenomenon in the Muslim world. Although Indonesia is not an Islamic state, it has legalized corporate zakat for nearly three decades. Baitulmaal Munzalan Indonesia (BMI), a prominent zakat management institution in West Kalimantan, actively collects corporate zakat despite the absence of this concept in classical fiqh (Islamic jurisprudence). This study examines the Islamic legal understanding of the ‘āmils (zakat administrators) at BMI and their practices in collecting corporate zakat through the Zakat BMI application. Employing a qualitative approach, this research is based on in-depth interviews with five key informants, as well as observations of the Zakat BMI application, official website, and social media platforms. The findings reveal that the ‘āmils at BMI conceptualize corporate zakat through qiyās (analogical reasoning), equating it with trade zakat (zakāh al-tijārah), a subcategory of wealth zakat (zakāt al-māl). Although corporate zakat is not explicitly mentioned in classical fiqh literature, BMI legitimizes its implementation by referencing Qur’anic verses, hadith, contemporary Islamic scholarly opinions, fatwas, and national legal regulations. Furthermore, BMI adopts the concept of a legal entity (shakhṣiyyah i‘tibāriyyah) as a zakat-liable subject, as developed by contemporary Islamic scholars, and applies this concept through various zakat collection programs, including the Zakat BMI application. This study highlights the necessity of contextual interpretation of zakat norms within classical fiqh to expand the scope of Islamic legal implementation in addressing modern socio-economic challenges while underscoring the evolving perception of Islamic law among Muslim societies, particularly concerning zakat regulations. [Zakat korporasi, atau zakat yang dikenakan pada entitas hukum, merupakan fenomena kontemporer dalam dunia Muslim. Meskipun Indonesia bukan negara Islam, negara ini telah melegalkan zakat korporasi selama hampir tiga dekade. Baitulmaal Munzalan Indonesia (BMI), sebagai salah satu lembaga pengelola zakat terkemuka di Kalimantan Barat, secara aktif menghimpun zakat korporasi meskipun konsep ini tidak ditemukan dalam literatur fikih klasik. Studi ini menganalisis pemahaman hukum Islam yang dimiliki oleh para amil zakat di BMI serta praktik penghimpunan zakat korporasi yang dilakukan melalui aplikasi Zakat BMI. Dengan menggunakan pendekatan kualitatif, penelitian ini mengandalkan wawancara mendalam dengan lima informan kunci serta observasi terhadap aplikasi kalkulator zakat, situs web resmi, dan media sosial BMI. Temuan penelitian menunjukkan bahwa para amil zakat di BMI mengonseptualisasikan zakat korporasi melalui qiyās (analogi) dengan menyamakannya dengan zakat perdagangan, yang merupakan bagian dari zakat mal. Meskipun zakat korporasi tidak disebutkan secara eksplisit dalam literatur fikih klasik, BMI membangun legitimasi atas penerapannya dengan merujuk pada ayat-ayat Alquran, hadis, pendapat ulama kontemporer, fatwa, serta regulasi hukum nasional. Selain itu, BMI mengadopsi konsep badan hukum (shakhṣiyyah i‘tibāriyyah) sebagai subjek hukum dalam zakat, sebagaimana dikembangkan oleh para ulama kontemporer, dan menerapkannya dalam berbagai program penghimpunan zakat, termasuk aplikasi Zakat BMI. Studi ini menegaskan pentingnya interpretasi kontekstual terhadap norma zakat dalam fikih klasik guna memperluas cakupan penerapan hukum Islam dalam menjawab tantangan sosial-ekonomi modern, sekaligus menyoroti perubahan pemahaman masyarakat Muslim terhadap hukum Islam, khususnya dalam aspek zakat.]